PENGGUNAAN OSMOTIKUM DALAM MENUNDA KERUSAKAN BENIH KAKAO (Theobroma cacao. L) - Yulistiati Nengsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Cacao seeds are recalcitrant seeds quickly lose its growing when not immediately dikecambahkan after the last of the parent plant. Cocoa seeds can not be dried below the critical water and not tolerant of low temperatures. Shipping cocoa seeds for long distances requires packaging and storage of seeds baikuntuk maintain its growth or seed viability remains high until the time comes for planting.This research has been carried out in the Laboratory of the Faculty of Agriculture, University of Batanghari Basics about 3 months from February 2014 until June 2014.This study used a completely randomized design environment consisting of a single factor, with the provision of treatment osmoticum PEG-6000 in the cocoa seeds are packaged in HDPE plastic ventilated 10%, with the level of brand osmoticum PEG-6000 as follows: P0 Without osmoticum packed in ventilated plastic 10 %, P1, osmoticum concentration of 15% in ventilated plastic containers in 10%, 30% P2 osmoticum concentration in ventilated plastic containers in 10%, 45% P3 osmoticum concentration in ventilated plastic containers in 10%.Treatment osmoticum PEG-6000 with 45% concentration can inhibit seed germination until day 21 of 9.67 and viability of seeds stored and vigornya still in good condition. Osmoticum PEG-6000 treatment with several concentrations of the cocoa seed parameters significantly affect the percentage of seed germination and the percentage of moldy seed in storage, but no real effect on germination percentage, vigor index and germination rate after storage.Keyword:  Osmotikum, rekalsitran, cocoa